EFFECT OF NATURAL AND SYNTHETIC SWEETENERS ON ASCORBIC ACID CONTENT AND BROWN INDEX OF SOME CITRUS JUICE ANALOGEOUS SYSTEMS - Mazin M. I. Al-Zubaidy (Mesopotamia Journal of Agriculture)
Synthetic model systems of single strength orange juice prepared by different types of natural and synthetic sweeteners (Mannitol, Sucrose, Fructose, Glucose) to study their effect on ascorbic acid degradation during storage at 25, 35 and 45Cْ for 4 months. Results showed that adding different kinds of sweeteners used in this study caused a decreasing effect in ascorbic acid degradation with different reduction ratio depending on the type of sweeteners (Mannitol >Fructose >Sucrose >Glucose). Increasing the time and temperature of the storage caused increasing in reduction ratio and K constant of ascorbic acid degradation with decreasing in activation energy which led to this increasing in Brown index especially at the end of storage period at 45 Cْ.